On the classification of the genera Labyrinthula, Schizochytrium and Thraustochytrium (Labyrinthulids and Thraustochytrids) - Moestrup, Øjvind (Academia Journal of Biology, 2019)
Species of the genera Labyrinthula, Schizochytrium, Thraustochytrium and related organisms have recently attracted attention in biotechnology, and here is a short note on how to classify these rather special organisms